Phylogenetic relationships between telmatobiinids (Anura, Ceratophryidae, Telmatobiinae) of central Andes based on morphology of larval and adult stages - Aguilar, César (2009)
Batrachophrynus and Telmatobius are the two genus of Telmatobiinae from the central Andes. Both genera have species with adaptations for life at high altitude in the Andes, with aquatic or semi-aquatic habits in creeks, lagoons and lakes. The objective of this study is to evaluate the phylogenetic relationships between Batrachophrynus and 13 species of Telmatobius from the central Andes using larval and adult morphology including diagnostic characters for Batrachophrynus and Telmatobius, and putative sinapomorphies for Telmatobius. The phylogenetic analysis showed 20 parsimonious trees with 56 steps length. The results of this study hypothesize that the species assigned to Batrachophrynus form a monophyletic group nested within Telmatobius. In this study, most of the synapomorphies that support Telmatobius (including Batrachophrynus) come from larval morphology and these sinapomorphies will probably support the whole genus.